Optimisation of aquaculture wastewater by halophytes cultivation - Berge, Daan Louis ten (2024)
This thesis represents a comprehensive assessment regarding the cultivation of halophyte Salicornia ramosissima within aquaculture effluent-based systems and use of different water sources commonly available at aquaculture farms as treatments. Halophytes, recognised for their ability to thrive in saline environments, are gaining popularity for their versatile applications including culinary uses and source of secondary compounds with biorefinery potential. The experimental study spanned 6 weeks in a greenhouse at the Aquaculture Research Station of Olhão, Portugal. The setup entailed two production systems: semi-hydroponics and substrate mixture system consisting of potting soil and mud from a semi-intensive fishpond. Four treatments were applied in both systems. These involved water sources containing salinities 10, 20, and 35 PSU, the latter sourced from a semi-intensive pond system. In these treatments, plants received supplementary fertiliser. Additionally, the 35 PSU treatment was tested without supplementary fertiliser. Other treatments included water from a nearby brackish well (20 PSU) and its mixture with freshwater (10 PSU). The study aimed to assess how the two production systems combined with varying salinities and nutrient levels affect the growth, biochemical properties and nutritional content of S. ramosissima. Results indicated that the mud-based substrate system consistently produced higher biomass across all salinities compared to the semi-hydroponics system, particularly at 35 PSU. In the semi-hydroponics system, plants performed better at moderate salinity (20 PSU), while performance was more restricted at lower and higher salinities. Additional fertiliser in the high salinities (35 PSU) did not seem to affect growth or nutritional properties of biomass. Secondary metabolites were generally higher in biomass without supplementary fertiliser. The mud-based system appeared more robust, indicating suitability for high salinity environments. These results indicate that S. ramosissima could be used to effectively optimise aquaculture wastewater and act as biofilter whilst producing valuable biomass in highly saline conditions, promoting circular economy.